The Structure in de quoi - Lefeuvre, Florence (Journal of French language studies, 2006)
The French structure comprising de quoi '(about) something' + infinitive is examined in two syntactic contexts: (1) governed by a verb in sentences of the type Il y a de quoi s'interroger! 'there's something to wonder about'; & (2) ungoverned, as seen in Jamais la France du tres haut ne s'est aussi bien portee que sous Jospin, de quoi irriter l'ex-Premier ministre 'not since the earliest times has France been as healthy as under Jospin, something to irritate the former prime minister'. Two possible analyses are envisaged according to the value of de, which may be considered a partitive article or a preposition; in the former case, how is the infinitive to be articulated with de quoi? In comparison with utterances of the type il a de qui tenir 'it runs in the family', where de qui 'resembling someone' functions as an essential indirect complement of the infinitive, de quoi assumes the function of circumstant. Finally, the usage of the structure in discourse is studied in terms of the infinitives used & the presence or absence of an anaphoric relation between the proform quoi & a predicative structure in the preceding utterance. Adapted from the source document